RELEVANSI PENDIDIKAN PESANTREN DENGAN PENDIDIKAN MODERN: studi analisis pemikiran KH. Hasyim Asy’ari - Muhammad Asrori Ma’sum (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
This article aims to elaborate the thoughts of KH. Hasyim Asy'ari about Islamic boarding school education as well as revealing aspects of modernity that are relevant to current educational conditions. The significance value of this research lies in the greatness of KH. Hasyim Asy'ari in changing the pesantren education system, starting from the intake of character that is moralistic in principle to the plains of institutionalization and curriculum. A major breakthrough that is impressive and remains relevant to the existence of education today. By referring to some of his literature and works, this paper combines theory of thought with policy action in the field through the existence of Pesantren Tebuireng, Jombang. The method used is a literature study (literature approach) with the type of qualitative research. The data is taken from articles, books and other documents. The data were analyzed using philological content analysis, in which the reading of KH's educational thoughts. Hasyim Asy'ari is associated with his current development. From the results of the study resulted in conclusions, 1) the source of educational thinking goals according to KH. Hasyim Asy'ari is to humanize in his position as a creation that gives birth to awareness to carry out his rights and obligations to God the creator of man, this is the embryo of the birth of character education; 2) Islamic education is not only religious knowledge in material terms, but also general knowledge. So the opening of the curriculum by accepting general material (non-religious) is needed by pesantren; 3) Islamic boarding schools must be responsive to the times, follow the flow of change without letting go of the dignity of the pesantren.